Metastasis of adenoid cystic carcinoma from a submandibular gland to the larynx. Issue 6 (December 2019) - Ishikawa, Tomohiko; Tateda, Masaru; Oshima, Hidetoshi; Sawada, Akari; Oka, Naomi; Suzuki, Hiroyoshi; Hashimoto, Sho
Abstract: The present article discusses the first reported case of adenoid cystic carcinoma (ACC) metastasis from a submandibular gland to the larynx. Both treatments of distant metastasis of ACC and secondary laryngeal tumor are challenging. Despite its slow progression, ACC is associated with high rates of local recurrence, distant metastasis, and poor prognosis. Patients with secondary laryngeal cancer often have other concurrent metastatic lesions. Therefore, treatment selection should consider the biological behavior of the tumor and characteristics of the laryngeal lesion, along with the general condition and quality of life of the patient. The patient (55-year-old female) had a history of ACC of the right submandibular gland, removed surgically 9 years prior to the present consultation. Follow-up showed multiple pulmonary metastases. The patient complained of dysphonia lasting 3 months. Following the diagnosis of ACC metastasis to the larynx (supraglottic) and a neck lymph node via biopsy, we performed partial laryngectomy, left neck dissection, and tracheotomy. Histopathological examination showed an increase in the tumor grade over time. Two months after discharge, there was no obvious local recurrence or increase in lung metastasis.